1996
DOI: 10.1164/ajrccm.153.2.8564143
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of angiotensin-converting enzyme gene in sarcoidosis.

Abstract: Sarcoidosis is the disease in which increased levels of serum Angiotensin-converting enzyme (sACE) are most often detected. It has recently been shown that the deletion (D) or the insertion (I) of a 250bp-DNA fragment in the ACE gene accounts for three main ACE genotypes (i.e., II, ID, and DD) and for 47% of total phenotypic variance in sACE level. The aim of our work was to investigate whether or not patients with sarcoidosis have an increased incidence of those ACE genotypes coding for highest sACE levels an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 12 publications
3
52
1
2
Order By: Relevance
“…The characteristics of 12 analyses (Arbustini et al 1996;Furuya et al 1996;Sharma et al 1997;Tomita et al 1997;Takemoto et al 1998;Garrib et al 1998;Maliarik et al 1998;Pietinalho et al 1999;Papadopoulos et al 2000;Planck et al 2002;Alia et al 2005) on the risk of sarcoidosis in subjects with intron16 ID polymorphism in the ACE gene are summarized in Table 2. These studies involved 1,392 patients and 2,147 controls.…”
Section: Results Of Id/ace Polymorphism In Sarcoidosismentioning
confidence: 99%
See 3 more Smart Citations
“…The characteristics of 12 analyses (Arbustini et al 1996;Furuya et al 1996;Sharma et al 1997;Tomita et al 1997;Takemoto et al 1998;Garrib et al 1998;Maliarik et al 1998;Pietinalho et al 1999;Papadopoulos et al 2000;Planck et al 2002;Alia et al 2005) on the risk of sarcoidosis in subjects with intron16 ID polymorphism in the ACE gene are summarized in Table 2. These studies involved 1,392 patients and 2,147 controls.…”
Section: Results Of Id/ace Polymorphism In Sarcoidosismentioning
confidence: 99%
“…2 The results of individual and summary OR estimates with 95% CI, fixed-effect model: (a) ID/ACE polymorphism-dominant genetic model; (b) ID/ACE polymorphism-recessive genetic model. The size of the square is proportional to the percent weight of each study; horizontal lines represent the 95% CI higher production of sACE in both the general population and sarcoidosis patients (Rigat et al 1990;Tiret et al 1992;Arbustini et al 1996;Furuya et al 1996;Sharma et al 1997;Tomita et al 1997;Csaszar et al 1997). All these findings have contributed to the idea of the ID/ACE polymorphism's involvement in sarcoidosis etiology and/or pathogenesis, but neither the individual studies (except for African Americans) nor our meta-analysis confirmed this idea.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Probably this polymorphism is the best characterized in sarcoidosis (table 2). 1) Genotype distribution is not different between patients with sarcoidosis and controls in the Caucasians groups studied: Italians [95], Americans [96], and Finnish [97]; 2) Contrasting results were achieved in the Japanese: no association was found in a large series of subjects from central Japan [98], whereas an early report found an excess of ID or DD genotypes among females patients (OR 2.18) [99]: 3) In marked contrast, the DD genotype was a significant risk factor for African-American sarcoid patients (OR 3.17), especially in those with a family history of the disorder [96]. 4) No correlation was found between ACE genotype and sarcoidosis parameters, such as chest radiograph stage, extrapulmonary involvement, and progression in Italian and Japanese patients, whereas a modest correlation was found between the II genotype and radiographic progression among the African-American patients [96].…”
Section: Angiotensin Converting Enzyme Genementioning
confidence: 90%